Latino college presidents in their own words - León, David J.; Martinez, Ruben Orlando (Emerald, 2013)
Latino college presidents : in their own words is a collection of autobiographical-professional essays by leading Latino and Latina presidents of colleges and universities across the country. Each has written a chapter based on their personal education and professional lives. The presidents divide their essays into three sections: 1) Surviving the educational pipeline to obtain an advanced degree, in which they detail their parents' support and at times sacrifices for their children's educational dreams; 2) Moving up the faculty/administrative ladders, in which they cite challenges they experienced and numerous examples from their backgrounds that helped them become successful professors and administrators; 3) Advice for up-and-coming administrators, in which they describe numerous projects they designed and implemented, often reflecting their parents' values and impact on their long careers.
Includes index.
Keywords: Company secretary: role & responsibilities.; Boards & directors: role & responsibilities.; Hispanic American college presidents -- United States -- Biography.; Education, Higher -- United States.; elektronické knihy; electronic books